Innovative psychometric modeling and methods - Jiao, Hong, 1968-; Lissitz, Robert W. (MARCES book series., 2020)
"The general theme of this book is to present the innovative psychometric modeling and methods. In particular, this book includes research and successful examples of modeling techniques for new data sources from digital assessments, such as eye-tracking data, hint uses, and process data from game-based assessments. In addition, innovative psychometric modeling approaches, such as graphical models, item tree models, network analysis, and cognitive diagnostic models, are included. Chapters 1, 2, 4 and 6 are about psychometric models and methods for the learning analytics. The first two chapters focused on advanced cognitive diagnostic models for tracking learning and the improvement of attribute classification accuracy. Chapter 4 demonstrated the use of network analysis for learning analytics. Chapter 6 introduced the conjunctive root causes model for the understanding of prerequisite skills in learning. Chapters 3, 5, 8, 9 are about innovative psychometric techniques to model process data. Specifically, Chapters 3 and 5 illustrated the usage of generalized linear mixed effect models and Item Tree Models to analyze eye-tracking data. Chapter 8 discussed the modeling approach of hint uses and response accuracy in learning environment. Chapter 9 demonstrated the identification of observable outcomes in the game-based assessments. Chapters 7 and 10 introduced innovative latent variable modeling approaches, including the graphical and generalized linear model approach and the dynamic modeling approach. In summary, the book includes both theoretical, methodological, and applied research and practices that serve as the foundation for future development. These chapters provide illustrations of efforts to model and analyze multiple data sources from digital assessments. When computer-based assessments are emerging and evolving, it is important that researchers can expand and improve the methods for modeling and analyzing the new data sources in order to better provide diagnostic information about the students. This book provides a useful resource to researchers who are interested in the development of psychometric methods to solve issues in this digital assessment age"--